Routing flood water through an irrigation delivery system - Roche, W. Martin, author; U.S. Committee on Irrigation and Drainage, publisher (Colorado State University. Libraries, 1992)
The Turlock Irrigation District, located in the Central Valley of California, supplies irrigation water to 150,000 acres and electricity to over 60,000 customers. The District's irrigation service area is highly developed, and most natural drainage channels have been eliminated. The irrigation delivery system, consisting of 250 miles of canals and laterals, is used by farmers and cities to route storm drainage during the wet season. There are two small intermittent streams, Sand Creek and Mustang Creek, that enter the canal system. During normal storm events, runoff is small and the canals can readily handle the flows from the two creeks, and storm water from Turlock, other communities, and farms. On February 12, 1992 an intense storm in the area resulted in rainfall accumulations of 2.5 inches to 3.5 inches in a 24-hour period. Rainfall of these intensities occurs less frequently than once every 100 years. By early afternoon it was obvious that large flows from the two streams would reach the canal system by evening. A command post was established and crews were organized to patrol the canals and to route flows to laterals with capacity available. In the early evening the Highline Canal had broken in five locations. Crews were immediately dispatched to begin repairs, and additional help was secured from local contractors and farmers. During the same period, the Turlock Main Canal was flowing at peak capacity, with flows being routed to several laterals. The City of Turlock had to discontinue pumping for almost 24 hours. By carefully routing the storm water and keeping the canals and laterals free of debris, additional major damage was avoided. As a result of this emergency, the Turlock Irrigation District is preparing a flood control manual for use in future flood events.
Irrigation and water resources in the 1990's
Not digitized by CSUL Digital Services.
Presented at Irrigation and water resources in the 1990's: proceedings from the 1992 national conference held on October 5-7, 1992 in Phoenix, Arizona.